2001
DOI: 10.1093/gerona/56.10.b432
|View full text |Cite
|
Sign up to set email alerts
|

Have the Oldest Old Adults Ever Been Frail in the Past? A Hypothesis That Explains Modern Trends in Survival

Abstract: Three important results concerning the shape and the trends of the human mortality rate were discussed recently in demographic and epidemiological literature. These are the deceleration of the mortality rate at old ages, the tendency to rectangularization of the survival curve, and the decline of the old age mortality observed in the second part of the 20th century. In this paper we show that all these results can be explained by using a model with a new type of heterogeneity associated with individual differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…A recently developed mathematical model explains the variation of heterozygosity in an ageing cohort in terms of differential survival as affected by the biological role of the gene. 19 According to the model, centenarians are expected to show increasing heterozygosity with respect to young subjects for stress-responder genes driving the individual adaptive capacity. Data in Table 1 suggest that PON1 is one of the genes affecting such adaptive capability, and therefore one of the genes affecting rate and quality of ageing.…”
Section: Discussionmentioning
confidence: 99%
“…A recently developed mathematical model explains the variation of heterozygosity in an ageing cohort in terms of differential survival as affected by the biological role of the gene. 19 According to the model, centenarians are expected to show increasing heterozygosity with respect to young subjects for stress-responder genes driving the individual adaptive capacity. Data in Table 1 suggest that PON1 is one of the genes affecting such adaptive capability, and therefore one of the genes affecting rate and quality of ageing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, children who attend daycare in their first few months are much less likely to develop leukemia than those who stay at home (Marshall 2008). Yashin et al (2001) raised the possibility that at least part of today's centenarians paradoxically originated from an initially frail part of the cohort. The authors suggested that an originally more vulnerable (and primarily more labile) organism may improve the quality of its own response to stress compared with an originally more robust (and primarily more stable) organism, because of a better-trained vascular and other systems.…”
Section: Early-life-induced Hormetic Effects In Human Populationsmentioning
confidence: 99%
“…However, as a complex trait, the heritability of 'lifespan' may be influenced by an interplay of genetic, environmental and stochastic factors. 14,15 In addition, the influence of the genetic component on lifespan is expected to be stronger in populations of areas where environmental factors are harsher 16 as demonstrated in different studies. 9,17,18 Calabria is one of the poorest Italian regions located in the southern part of the peninsula.…”
Section: Introductionmentioning
confidence: 98%